BUILDING THE BLUE OCEAN STRATEGY THROUGH THE TECHNIQUES OF MARKETING INTELLIGENCE/ AN EXPLORATORY STUDY IN IRAQI PRIVATE BANKS (World Economics and Finance Bulletin, 2023)
Current trends in business management emphasize the increasing importance of information to support the various activities of business organizations in general and service in particular, especially as these organizations operate in an environment of turmoil and rapid change as well as fierce competition, which has made these organizations adopt a new strategy capable of innovating A new value that enables them to achieve excellence, in the banking industry and away from competitors, the current research focused on how to strengthen the strategy of the Blue Ocean in the banking industry by adopting the technology of marketing intelligence, The problem of research is to determine the extent to which banking organizations understand the importance of marketing intelligence in enhancing its blue strategy through the creation of new value, whether in current markets or new markets. The hypotheses were analyzed by analyzing the questionnaire distributed to 60 employees of the Middle East Bank for Investment, Finance and Golf Commercial Bank, Through SPSS, 22, the research reached a number of conclusions, the most important of which is that the techniques of marketing intelligence have a significant impact in enhancing the strategy of the Blue Ocean to create a new value to achieve excellence in the banking industry. The study concluded with a number of recommendations, the most important of which is the need to increase attention to the techniques of marketing intelligence without discrimination to promote innovative banking activities.